A broadband, self-powered, and polarization-sensitive PdSe₂ photodetector based on asymmetric van der Waals contacts - Zhang, Xuran (2023)
Self-powered photodetectors with broadband and polarization-sensitive photoresponse are desirable for many important applications such as wearable electronic devices and wireless communication systems. Recently, two-dimensional (2D) materials have been demonstrated as promising candidates for self-powered photodetectors owing to their advantages in light–matter interaction, transport, electronic properties, and so on. However, their performance in speed, broadband response, and multifunction is still limited. Here, we report a PdSe2 photodetector with asymmetric van der Waals (vdWs) contacts formed by using a homojunction configuration. This device achieves a high responsivity approaching 53 mA/W, a rise/decay time of about 0.72 ms/0.24 ms, and a detectivity of more than 5.17 × 1011 Jones in the visible-near infrared regime (532–1470 nm). In addition, a linear polarization-sensitive response can be observed with an anisotropy ratio of 1.11 at 532 nm and 1.62 at 1064 nm. Furthermore, a strong anisotropic response endows this photodetector withoutstanding polarization imaging capabilities, realizing a contrast-enhanced degree of linear polarization imaging.Our proposed device architecture demonstrated the great potential of PdSe2-based asymmetric vdWs contacts for high-performance photodetectors operating without any external bias.